2021
DOI: 10.9734/ajacr/2021/v8i330192
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Optimization of Biodiesel Produced from Palm Oil Using Acidified Clay Heterogeneous Catalyst

Abstract: The objective of the present work is to synthesize and characterizethe production of biodiesel from palm oil. Acid activated heterogeneous catalyst was used in the synthesis process. The clay was characterized using SEM. The effect of process variables such as reaction temperature, catalyst weight and oil to alcohol ratio were investigated. Response surface methodology (RSM) was utilized in the design of experiment and modeling of the biodiesel production process. The biodiesel was characterized and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The normal plot of residuals indicated that the residuals points were closely aligned within the straight line with few points lying outside the diagonal in a reasonable manner, which showed that the residuals were normally distributed. This relationship is significant because it ensures that the predicted values will show little deviation from the experimental values (Ezedinma et al., 2021; Ijeoma et al., 2021). The external residual plots showed that the residuals aligned closely to the null point within a distance of ±2.1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal plot of residuals indicated that the residuals points were closely aligned within the straight line with few points lying outside the diagonal in a reasonable manner, which showed that the residuals were normally distributed. This relationship is significant because it ensures that the predicted values will show little deviation from the experimental values (Ezedinma et al., 2021; Ijeoma et al., 2021). The external residual plots showed that the residuals aligned closely to the null point within a distance of ±2.1.…”
Section: Resultsmentioning
confidence: 99%
“…Figure7showed two factor interactions of the drying parameters obtained in both the RSM and ANFIS modeling. The three-D (3D) surface and contour plots can be used to visualize and interpret the nature of the synergetic relationship between two combined experimental parameters and the response(Ijeoma et al, 2021). The generation of the contour plots involved the variation of two input factors within the range of experiments while keeping the other constant at its null point.…”
mentioning
confidence: 99%